Impact of a goal-directed fluid therapy on length of hospital stay and costs of hepatobiliarypancreatic surgery: a prospective observational study. (19th November 2018) - Torregiani, Giulia; Claroni, Claudia; Covotta, Marco; Naccarato, Alessia; Canfora, Marco; Giannarelli, Diana; Grazi, Gian L; Tribuzi, Susanna; Forastiere, Ester
Aim: The effectiveness of goal-directed fluid therapy (GDFT) algorithms in improving postoperative outcomes has extensively been suggested. Nevertheless, there is a lack of strong evidence regarding both the clinical impact and the cost–effectiveness of the GDFT protocols. The aim of this study is to evaluate the costs of patients undergoing hepatobiliopancreatic surgery when a GDFT protocol is applied.Materials & methods: Consecutive ASA I–III patients undergoing hepatobiliopancreatic surgery were included in this prospective observational study. Depending on device availability, patients were handled either by fluid therapy guided by Vigileo monitor-derived hemodynamic variables (Vigileo–GDFT group) or by standard fluid treatment (standard group). Postoperative length of stay and economic costs were analyzed.Results: In total, 147 patients were included (71 in the Vigileo–GDFT group and 76 in the standard group). The total hospital length of stay was 13 (median, 1st–3rd quartile, 9–20) days for the Vigileo–GDFT group and 14 (8–21) days for the standard group (p = 0.58); no statistically significant differences between the two groups emerged regarding costs and postoperative complications. In both groups, complications were the main contributor to total cost sustained.Conclusion: The application of a GDFT algorithm did not reduced the total length of hospital stay and the global costs, which were mainly influenced by the number of complications.